SWEDISH GRACE 100 YEARS - A search for long lasting architectural qualities - Larsson, David (My University, 2020)
The construction industry, including architects, face a big challenge when it comes to sustainability. A part of the challenge is to build long-lasting architecture, that can stand the test of time and offer a high level of architectural qualities. The thesis aims to increase knowledge about long-lasting architecture through a case study of the now one hundred year old style of Swedish Grace. The following research questions will be in focus: 1. What are the architectural qualities of the older housing stock in Sweden, focusing on the 1920’s? 2. In what way can the architectural qualities of the 1920’s building stock in Sweden be interpreted into a contemporary project? The project will commence using research on design as a method to discover and study the qualities of older housing. The second part will focus on research by design to create a design proposal by interpreting the found qualities into a multi-family housing building.